Catalyst-free sulfenylation of indoles with sulfinic esters in ethanol. Issue 16 (30th July 2018) - Yang, Xiuqin; Bao, Yishu; Dai, Zonghao; Zhou, Qingfa; Yang, Fulai
Abstract : A novel catalyst-free method for the synthesis of structurally diverse indole thioethers in moderate to excellent yields. Abstract : A novel catalyst-free method for the synthesis of structurally diverse indole thioethers in moderate to excellent yields has been developed. In this reaction, sulfinic esters serve as new sulfur electrophiles.